Cosmogenic nuclide weathering biases: corrections and potential for denudation and weathering rate measurements - R. F. Ott; S. F. Gallen; D. E. Granger (Geochronology, 2022)
Cosmogenic radionuclides (CRNs) are the standard tool to derive centennial-to-millennial timescale denudation rates; however, it has been demonstrated that chemical weathering in some settings can bias CRNs as a proxy for landscape denudation. Currently, studies investigating CRN weathering biases have mostly focused on the largely insoluble target mineral quartz in felsic lithologies. Here, we examine the response of CRN build-up for both soluble and insoluble target minerals under different weathering scenarios. We assume a simple box model in which bedrock is converted to a well-mixed regolith at a constant rate, and denudation occurs by regolith erosion and weathering either in the regolith or along the regolith–bedrock interface, as is common in carbonate bedrock. We show that weathering along the regolith–bedrock interface increases CRN concentrations compared to a no-weathering case and how independently derived weathering rates or degrees can be used to correct for this bias. If weathering is concentrated within the regolith, insoluble target minerals will have a longer regolith residence time and higher nuclide concentration than soluble target minerals. This bias can be identified and corrected using paired-nuclide measurements of minerals with different solubility coupled with knowledge of either the bedrock or regolith mineralogy to derive denudation and long-term weathering rates. Similarly, single-nuclide measurements on soluble or insoluble minerals can be corrected to determine denudation rates if a weathering rate and compositional data are available. Our model highlights that for soluble target minerals, the relationship between nuclide accumulation and denudation is not monotonic. We use this understanding to map the conditions of regolith mass, weathering, and denudation rates at which weathering corrections for cosmogenic nuclides become large and ambiguous, as well as identify environments in which the bias is mostly negligible and CRN concentrations reliably reflect landscape denudation. We highlight how measurements of CRNs from soluble target minerals, coupled with bedrock and regolith mineralogy, can help to expand the range of landscapes for which centennial-to-millennial timescale denudation and weathering rates can be obtained.